2017
DOI: 10.1038/s41598-017-16493-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide meta-analysis in Japanese populations identifies novel variants at the TMC6–TMC8 and SIX3–SIX2 loci associated with HbA1c

Abstract: Glycated haemoglobin (HbA1c) is widely used as a biomarker for the diagnosis of diabetes, for population-level screening, and for monitoring the glycaemic status during medical treatment. Although the heritability of HbA1c has been estimated at ~55–75%, a much smaller proportion of phenotypic variance is explained by the HbA1c-associated variants identified so far. To search for novel loci influencing the HbA1c levels, we conducted a genome-wide meta-analysis of 2 non-diabetic Japanese populations (n = 7,704 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 73 publications
(93 reference statements)
2
20
0
Order By: Relevance
“…We also excluded subjects who had inconsistent sex information between the genotype and questionnaire, who had an estimated non-Japanese ancestry, or who had a low call rate (<0.95) [ 16 , 17 ]. Furthermore, we excluded the close relationship pairs determined using the identity-by-descent method (PI_HAT > 0.1875) according to previous studies [ 8 , 13 , 18 , 19 ]. Quality control analyses were carried out using PLINK [ 20 , 21 ] (version 1.90b3.42) and Eigensoft [ 16 ] (version 6.1.3).…”
Section: Methodsmentioning
confidence: 99%
“…We also excluded subjects who had inconsistent sex information between the genotype and questionnaire, who had an estimated non-Japanese ancestry, or who had a low call rate (<0.95) [ 16 , 17 ]. Furthermore, we excluded the close relationship pairs determined using the identity-by-descent method (PI_HAT > 0.1875) according to previous studies [ 8 , 13 , 18 , 19 ]. Quality control analyses were carried out using PLINK [ 20 , 21 ] (version 1.90b3.42) and Eigensoft [ 16 ] (version 6.1.3).…”
Section: Methodsmentioning
confidence: 99%
“…S7 ). Expression quantitative trait locus (eQTL) analysis using Japanese multi-omics iMETHYL datasets 25 , 32 , 33 showed that the rs8022678 A allele was weakly associated with decreased BCL11B expression level in CD4 + T cells (Supplementary Fig. S8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that the 3′- BCL11B gene desert region harbours several remote enhancers that modulate BCL11B gene expression 34 , 35 . Japanese multi-omics iMETHYL datasets 25 , 32 , 33 showed that the rs8022678 A allele was weakly associated with decreased BCL11B expression level in CD4 + T cells. Some variants at the 3′- BCL11B gene desert region were associated with aortic stiffness and cardiovascular disease risk 36 , although rs8022678 was not linked with those variants by linkage disequilibrium ( r 2 = 0.002 in East Asians according to the LDlink server 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations